Learning by watching Vernacular Iñupiaq-Inuit design learning as inspiration for design education - Reitan, Janne Beate (Høgskolen i Oslo og Akershus, 2014)
In this article , I explore a single case of vernacular clothing design — the practice and learning of design for contemporary Iñupiaq - Inuit clothing made by women from Kaktovik in N orth ern Alaska — and I hope to contribute to a better understanding of design practice and learning in general. Design research has many unexplored areas , and one of these omissions is vernacular design , or folk design. In my opinion, professional and academic design may well have something to learn from vernacular design, although this research is about vernacular learning and about what, why and how the ‘making ’ discipline of clothing design is learned . Th i s study was based on observations of and interviews with seamstresses and research - by - design , which includes authorial participation in designing and sewing in adherence to Iñupiaq tradition . A ll of this was recorded on digital video film. Th e investigatio n of Iñupiaq - Inuit clothing design indicates that watching wa s the most common way of learning , a phenomenon I have chosen to call learning - by - watching , a concept that can be seen as a development of both Schön and Wenger’s theories of learning , as influen ced by John Dewey’s theory of learning - by - doing . This study will be discussed in connection with design education , from kindergarten to professional studies in higher education , in the forth coming research project , Design Literacy , t he purpose of which is to develop theory to improve design education in both compulsory and academic design education. Consequently, to improve design education in general , a th o rough focus on learning - by - watching in communities of practice would make for more reflective practit ioners and more sustainable design practices in the long run. This work is licensed under a Creative Commons Attribution 4.0 International License